Cyber crimes - DeAngelis, Gina; Sarat, Austin (Philadelphia, Pa. : Chelsea House Publishers, 2000)
Discusses the high tech crimes committed by hackers, crackers, and phone phreaks using computers, including fraud, embezzlement, and espionage, as well as the best ways to minimize the occurrence of such crimes
References p. 92-97
Keywords: Computer crimes -- United States -- Juvenile literature